Transportation Cost Analysis for Carton Box Shipments via On-Call Car Rental - Haniifah Octaviani; Wanta Wanta; Dwi Epty Hidayaty (Transpublika Publisher, 2025)
Transportation costs present a significant challenge in managing company operations, particularly within the goods distribution sector. This study aims to analyze the efficiency of carton box shipping transportation costs during the period 2022 to 2024 by using on-call car rental services. The research method used is descriptive quantitative with the application of mathematical models to calculate the average monthly transportation costs. The data analyzed is secondary data from the company's financial statements that have been systematically processed. The results showed that there were significant fluctuations in transportation costs each year. The year 2023 was recorded as the most efficient period with an average cost of IDR 166,486,233 per month, compared to IDR 177,965,600 in 2022 and IDR 213,813,716 in 2024. The efficiency in 2023 shows the success of the transportation management strategy, while the increase in costs in 2024 is due to a surge in shipment volumes and rising fuel prices. This study concludes that the utilisation of on-call car rental services can serve as an efficient solution, provided it is backed by optimal logistics planning. The implications of these findings highlight the necessity for periodic evaluation of the transportation methods employed to sustain operational cost efficiency amidst fluctuating demand and pricing dynamics.